Quantophrenia – a scientist in numbers and numbers in science - Mićanović, Aleksandar (Sociološki pregled, 2025)
The book deals with the topic of quantophrenia, a growing and finally prevailing practice of the quantification of social sciences through counting papers and, on that basis, measuring their influence via scientific indices, which further creates the need for publishing as many papers as possible in adequate places, while the content quality of those papers falls into the background – the quantity of scientific papers is imposed as quality.
Keywords: quantophrenia; quantification; scientometrics; productivity